History of Nepalese Tourism Industry - Bhandari, Arjun Bahadur (Kalika Journal of Multidisciplinary Studies, 2022)
Tourism is not a new phenomenon in Nepal. People had been travelling by different means since ancient times when the modern concept of tourism was not introduced. Due to the Rana autocracy, Nepal was closed to the international visitor. After the restoration of democracy in 1950 Nepal government has recognized tourism as a key vehicle of development. Many developing countries are incorporating tourism into their industrial value and government of Nepal also has recognized tourism is as a high-paying industry and a key source of revenue which was priorities in tourism policy. Nepal’s Tourism Policy-2009 focuses on enhancing quality, accumulating foreign reserves, and creating job opportunities to help Nepalese people improve their living conditions and protecting environment for its sustainability. Nepali tourism saw ups and downs between1999 to 2021; including an Indian plane hijacking, a Royal massacre, a decade-long Maoist insurgency, an international economic crisis, the 2015 earthquake, and the COVID-19 epidemic. Since its inception, the Nepali tourist sector has struggled. Despite the government’s priority, the private sector has established itself as a high-paying enterprise. This article is based on qualitative research and aims to address historical development of tourism in Nepal. Descriptive and analytical methods were used in this research to investigate the history of Nepali tourism industry. In-depth interviews and library research are being used to gather data about the subject. It is limited to historical study on the subject. Finding of the research can be generalized to study the entire situation of tourism in Nepal.